Assessment of the effects of supplementing rabbit diets with a culture of saccharomyces cerevisiae using performance, blood composition and clinical enzyme activities (1999)
The effects of dietary supplementation with a pure culture of Saccharomyces cerevisiae at 0.0, 1.5 and 3.0 g kg−1 on growth performance, blood composition and clinical enzyme activities in serum of rabbits were studied during a 56-day experiment. Rabbits fed 3.0 g kg−1 attained the heaviest (P < 0.05) body weight, consumed the highest (P < 0.05) quantity of feed and had the best (P < 0.05) feed conversion. Rabbits fed 1.5 g kg−1 yeast had higher (P < 0.05) body weight, feed intake and feed conversion efficiency than the unsupplemented group. The haematocrit, erythrocytes, haemoglobin, serum albumin: globulin ratio, and erythrocytic indices in rabbits fed 3.0 g kg−1 were superior (P < 0.05) to the unsupplemented group. Other haematological indices were similar (P > 0.05); but differential populations of lymphocytes were fewer (P < 0.05) and monocytes and eosinophils were larger (P < 0.05) in rabbits fed the basal group. Serum Ca2+, globulin, cholesterol, aspartate and alanine aminotransferases, and alkaline phosphatase were higher (P < 0.05) in the basal group than with the yeast-supplemented diets. The data obtained suggest that yeast addition significantly improved growth performance, enhanced haematopoiesis, reduced serum cholesterol and maintained the serum enzymes at normal ranges. Furthermore, the activities of the clinical enzymes suggested liver- and bone-specific advantages from supplemental yeast. The effects of yeast were dose-dependent, and there is a need to determine the economically optimum dietary concentration.